Система оценки деятельности оператора при дистанционном обучении на компьютерном тренажере - Тимофеев, В. А.; Тулупов, В. В. (УАДО, 2004)
The principles of building and structure of a computer training simulator for efficient-dispatch personnel for gas-transport systems (GTS) is considered and its mathematical foundation elements are developed. Analysis of GTS as an automated control object is performed. The need for training simulators for the technological process operators is shown.
Keywords: дистанционное обучение; компьютерный тренажер